Core‐Shelled Nanoparticle Fillers for Recoverable Magnetic Liquid Metal with High Stability. Issue 4 (30th October 2022) - Huang, Mingdeng; Lin, Weiguang; Tuersun, Yisimayili; Huang, Xu; Chu, Sheng
Abstract: Room‐temperature liquid metals, such as galinstan, have become an emerging material in electronics requiring stretchability and deformability due to its excellent fluidity and conductivity. Eutectic gallium‐indium‐tin (galinstan)‐based composites with certain metallic fillers can obtain magnetism. However, the alloying reaction between galinstan and metals leads to the solidification and reduction in stability of the composite. In this study, Ni@SiO2 nanoparticles with the core–shell structure are used as fillers and galinstan as matrix. The obtained galinstan‐Ni@SiO2 paste is fairly stable and this is attributed to the silica shell, which acts as a barrier to isolate the direct contact between the Ni and galinstan. In addition, flexible circuits composed of as‐prepared galinstan‐Ni@SiO2 pastes are fabricated, which exhibited outstanding durability, retrievability, and self‐healing ability under the drive of magnetic field. Abstract : A feasible strategy to prepare recoverable galinstan‐based pastes, which maintains the homogenous paste‐like state and magnetism for a long time, is proposed in this paper. With the advantages, as‐prepared pastes were successfully applied to flexible circuits as conductors. And the circuits possess high performance, including excellent durability, retrievability, and self‐healing ability.